2014
DOI: 10.2215/cjn.05320513
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Ferumoxytol and Iron Sucrose for Treating Iron Deficiency Anemia in Patients with CKD

Abstract: Background and objectives Few randomized controlled trials have compared intravenous iron products head to head in CKD patients with iron deficiency anemia. This study compared the efficacy and safety of two intravenous iron products (ferumoxytol [Feraheme injection] and iron sucrose [Venofer]) in patients with CKD and iron deficiency anemia.Design, setting, participants, & measurements In this phase II, randomized, open-label, active-controlled, multicenter clinical trial, patients were randomized 1:1 to eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
89
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 11 publications
4
89
0
1
Order By: Relevance
“…The authors concluded that when HMW iron dextran is avoided, the other formulations are safe with a SAE rate of less than 1:200,000 administrations [43]. This is supported by two published prospective studies and a meta-analysis comparing LMW iron dextran and IS [44][45][46], two prospective comparisons of ferumoxytol and IS [47,48], and a retrospective observational analysis [49], all of which found no significant difference in adverse events among the various formulations. Consistent with these data, Wysoski et al, using the IMS Database (a pharmaceutical marketing research company whose data are based on sales of products moving from manufacturers into various outlets), FDA reporting system MedWatch, emergency room visits and death certificates obtained from the National Center for Health Statistics, concluded it is impossible, using current monitoring systems, to tell the relative rates of SAEs absent head-to-head trials [50].…”
Section: Safety Issuesmentioning
confidence: 87%
“…The authors concluded that when HMW iron dextran is avoided, the other formulations are safe with a SAE rate of less than 1:200,000 administrations [43]. This is supported by two published prospective studies and a meta-analysis comparing LMW iron dextran and IS [44][45][46], two prospective comparisons of ferumoxytol and IS [47,48], and a retrospective observational analysis [49], all of which found no significant difference in adverse events among the various formulations. Consistent with these data, Wysoski et al, using the IMS Database (a pharmaceutical marketing research company whose data are based on sales of products moving from manufacturers into various outlets), FDA reporting system MedWatch, emergency room visits and death certificates obtained from the National Center for Health Statistics, concluded it is impossible, using current monitoring systems, to tell the relative rates of SAEs absent head-to-head trials [50].…”
Section: Safety Issuesmentioning
confidence: 87%
“…11 The only prospective trial to report a significant safety difference between any of the formulations compared the now unavailable HMWID to ferric carboxymaltose and erroneously concluded, without differentiating the high and low molecular weight formulations, that ferric carboxymaltose had a safety advantage over iron dextran.…”
mentioning
confidence: 99%
“…If minor infusion reactions occur with one formulation, switching to another is appropriate and safe. Christian Breymann, 4 Steven Fishbane, 5 Anat Gafter-Gvili, 6 Christoph Gasche, 7 Jeffrey Gilreath, 8 Giuliano Grazzini, 9 David Henry, 10 Giancarlo Liumbruno, 11 Francesco Locatelli, 12 Iain Macdougall, 13 Manuel Munoz, 14 David Rampton, 15 George Rodgers, 16 and Aryeh Shander …”
mentioning
confidence: 99%
“…Macrocytic is when MCV >91 fl. 18 In microcytic aneamia, serum iron is decreased and total iron binding capacity (TIBC) is increased. The serum ferritin level indicates iron stores in the body.…”
Section: Discussionmentioning
confidence: 99%